Application of Meaningful Learning by Teachers to Improve Learning Outcomes of Citizenship Education - Irna Silawane; Aisa Abas; Jumiati Tuharea (CV. Rayyan Dwi Bharata, 2023)
This research was conducted based on the findings of problems found in SMP N 105, Central Maluku Regency. It is known that the learning outcomes of Citizenship Education for class VII students of SMP Negeri 105 Maluku Tengah are still low for Civics subjects. This is caused because the teacher applies the lesson method which watches without change during the learning process so that there are still many who have not reached the minimum completeness criteria (KKM) that have been determined by the teacher or the school, namely â‰¥70. The purpose of this study was to find out the application of Meaningful learning by teachers to improve Civics learning outcomes in class VII at SMP N 7 Tehoru, Tehoru District, Central Maluku Regency. The method used in this research is a class action research (CAR). Classroom action research is research conducted by educators in collaboration with researchers, or by educators who act as researchers in the classroom or at the school where they teach, with an emphasis on perfecting or improving learning processes and practices. Data collection techniques in this study are observation, tests and documentation. The results of this study indicate that there is an increase in Civics learning outcomes by using Meaningful Learning in Class VII at SMP N 105 Central Maluku.